Z-4.3=1.6

Simple and best practice solution for Z-4.3=1.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z-4.3=1.6 equation:


Simplifying
Z + -4.3 = 1.6

Reorder the terms:
-4.3 + Z = 1.6

Solving
-4.3 + Z = 1.6

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '4.3' to each side of the equation.
-4.3 + 4.3 + Z = 1.6 + 4.3

Combine like terms: -4.3 + 4.3 = 0.0
0.0 + Z = 1.6 + 4.3
Z = 1.6 + 4.3

Combine like terms: 1.6 + 4.3 = 5.9
Z = 5.9

Simplifying
Z = 5.9

See similar equations:

| x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 | | 3x-2=8x-1 | | 6.43-10d=2.5 | | -2c+5=-c+2 | | 9x+15=14x-11 | | 2a-17+20a-9= | | -2(2k-4)=4(k-2) |

Equations solver categories